Effects of secretome supplementation on interleukin-6, tumor necrosis factor-α, procalcitonin, and the length of stay in acute exacerbation COPD patients - Fahlevie, Fahlevie; Apriningsih, Hendrastutik; Sutanto, Yusup S.; Reviono, Reviono; Adhiputri, Artrien; Aphridasari, Jatu; Prasetyo, Windu (Narra J, 2023)
Acute exacerbation chronic obstructive pulmonary disease (AECOPD) is associated with significant poor survival. Mesenchymal stem cells (MSC) therapy has been a promising treatment for COPD; therefore, it has the potential to be an additional therapy for AECOPD. Its potential is associated with its secretome since it has anti-inflammatory and immunomodulator activities. The aim of this study was to determine the effect of the secretome as an adjuvant therapy in reducing the levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), procalcitonin, and the length of stay in AECOPD patients. A clinical control trial study was conducted among 28 moderate and severe AECOPD patients who were hospitalized from January to February 2023. The control group (n=14) received standard therapy of AECOPD while the treatment group (n=14) received standard therapy plus secretome 1 ml twice daily for three days. The levels of IL-6, TNF-α, and procalcitonin were measured at admission and on the fourth day of treatment. The length of stay was calculated from the time the patient was admitted until the patient was discharged from hospital. The data were compared using a paired Student t-test, chi-squared test and Mann-Whitney test as appropriate. In the treatment group, the levels of IL-6, TNF-α and procalcitonin after the treatment reduced 13.09 pg/mL, 5.00 pg/mL and 751.26 pg/mL, respectively compared to pre-treatment. In contrast, the levels of IL-6, TNF-α and procalcitonin increased 48.56 pg/mL, 44.48 pg/mL and 346.96 pg/mL, respectively after four days of treatment. There was a significant reduction of IL-6, TNF-α and procalcitonin in treatment group compared to the control group with p=0.022, p=0.009 and p=0.001, respectively. However, there was no significant reduction of the length of stay (p=0.072). In conclusion, administration of secretome to AECOPD patients could reduce the levels of IL-6, TNF-α and procalcitonin.